2023
DOI: 10.1093/europace/euac261
|View full text |Cite
|
Sign up to set email alerts
|

Improved prediction of sudden cardiac death in patients with heart failure through digital processing of electrocardiography

Abstract: Aims Available predictive models for sudden cardiac death (SCD) in heart failure (HF) patients remain suboptimal. We assessed whether the electrocardiography (ECG)-based artificial intelligence (AI) could better predict SCD, and also whether the combination of the ECG-AI index and conventional predictors of SCD would improve the SCD stratification among HF patients. Methods and results In a prospective observational study, 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“… 22 Second, new tools such as machine learning may improve statistical performance of models since they have been shown to outperform traditional models in various areas. 23 Third, the integration of signal analysis by artificial intelligence may represent a major advance in this our field. 24 Altogether, these approaches might lead to better risk stratification and therefore earlier detection of high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“… 22 Second, new tools such as machine learning may improve statistical performance of models since they have been shown to outperform traditional models in various areas. 23 Third, the integration of signal analysis by artificial intelligence may represent a major advance in this our field. 24 Altogether, these approaches might lead to better risk stratification and therefore earlier detection of high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…In some published AI-driven FCHD or SCD prediction research, very high accuracies (AUC>0.85) were achieved hours before the event, which reduces usability for therapeutic interventions as well as they are not applicable to population level screening 5,15,29 . However, results from our research show sustained high AUC of 0.91 for 2-year risk prediction of FCHD.…”
Section: Discussionmentioning
confidence: 99%
“…There is potential for the development of AI models for pre-screening during any clinical service to assess the risk of FCHD/SCD at an early enough stage to allow for prevention or timely therapeutics. Current research has tried to predict FCHD risk using clinical risk factors 14 , ECG features as biomarkers 5,15 , cardiac imaging 16,17 and have also made available a 5-year SCD risk calculator which is specific to people with hypertrophic cardiomyopathy 14 but these have limitations attributed to prediction performance, small sample sizes or require additional resources, which might not be accessible to everyone.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review and exploratory metanalysis of 46 studies that used electrophysiological signals to predict malignant VAs concluded that the AI models developed achieved a high performance, and that there is potential for the personalized prediction of malignant VA, although significant methodical limitations were identified in multiple studies [ 71 ]. AI-ECG applied to heart failure patients was found to be more discriminatory than conventional methods in determining SCD, especially in patients with an LVEF range of 35–50% and NICMP, and was able to discriminate between SCD and non-SCD [ 72 ].…”
Section: Risk Vs Benefit Of Icdsmentioning
confidence: 99%